2009
DOI: 10.4049/jimmunol.182.3.1577
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Deficiency Compromises Parasite Survival in Chronic Nematode Infection

Abstract: Immune responses elicited by parasitic worms share many features with those of chronic allergy. Eosinophils contribute to the inflammation that occurs in both types of disease and helminths can be damaged or killed by toxic products released by eosinophils in vitro. Such observations inform the widely held view that eosinophils protect the host against parasitic worms. The mouse is a natural host for Trichinella spiralis, a worm that establishes chronic infection in skeletal muscle. We tested the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
138
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 35 publications
(54 reference statements)
12
138
0
5
Order By: Relevance
“…Basophils have an important role in the allergic process, while eosinophils play a major role in the process of infection by parasitic worms. (19) The average value of basophils from this study ranged from 0 to 0.4%. These results do not show significantly different increases from the physiological value of basophils of 0 to 0.3%.…”
Section: Discussionmentioning
confidence: 66%
“…Basophils have an important role in the allergic process, while eosinophils play a major role in the process of infection by parasitic worms. (19) The average value of basophils from this study ranged from 0 to 0.4%. These results do not show significantly different increases from the physiological value of basophils of 0 to 0.3%.…”
Section: Discussionmentioning
confidence: 66%
“…Underlying causes for the WBC abnormalities seen in the dogs are uncertain, but eosinophilia is often attributable to ectoparasites or other macroparasites, such as helminths (Fabre et al 2009). Leukocytosis and lymphocytosis may be due to epinephrine-mediated responses associated with blood collection or in some instances, inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (2012) observed eosinophils around the nurse cells 4 weeks p.i. Eosinophils are not necessary for killing larvae and a recent study suggested that eosinophils may affect the immune response in a manner that would sustain chronic infection and ensure worm survival within the host (Fabre et al, 2009). T. spiralis muscle larvae death was correlated with enhanced IFN-γ and reduced IL-4 production (Kang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%